2021
DOI: 10.1016/j.arth.2020.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness, Patient Satisfaction, and Cost Reduction of Virtual Joint Replacement Clinic Follow-Up of Hip and Knee Arthroplasty

Abstract: Background Total hip and knee arthroplasties are increasingly performed operations, and routine follow-up places huge demands on orthopedic services. This study investigates the effectiveness, patients’ satisfaction, and cost reduction of Virtual Joint Replacement Clinic (VJRC) follow-up of total hip arthroplasty and total knee arthroplasty patients in a university hospital. VJRC is especially valuable when in-person appointments are not advised or feasible such as during the COVID-19 pandemic. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
36
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 22 publications
(37 reference statements)
6
36
1
Order By: Relevance
“…Logically speaking, the review of concept and theoretical notions should take place prior to the measurement of this construct, while the analysed papers studied patient satisfaction in the reverse order. There were also papers in which satisfaction was not defined at all [43,[46][47][48][49]53,56,61,[64][65][66][67]72,80]. Taking into account both the survey questionnaires developed by the authors as well as well-defined, known, validated and reliable measures, these treat satisfaction as a multi-dimensional construct.…”
Section: Recommendations For Preparing Research On Patient Satisfaction With Remote Healthcarementioning
confidence: 99%
“…Logically speaking, the review of concept and theoretical notions should take place prior to the measurement of this construct, while the analysed papers studied patient satisfaction in the reverse order. There were also papers in which satisfaction was not defined at all [43,[46][47][48][49]53,56,61,[64][65][66][67]72,80]. Taking into account both the survey questionnaires developed by the authors as well as well-defined, known, validated and reliable measures, these treat satisfaction as a multi-dimensional construct.…”
Section: Recommendations For Preparing Research On Patient Satisfaction With Remote Healthcarementioning
confidence: 99%
“…One study showed that virtual follow-up after TKA that consisted of a patient questionnaire and x-rays at 5 yearly intervals avoided 1814 clinic appointments, which was equal to greater than 300 hours of clinic time without compromising patient safety [17]. El Ashmawy et al [16] found that 86% of patients undergoing virtual TJA consultation reported they had saved time and/or money, with 23% saying they saved travel time and 21% reporting less wait time. A recent study conducted in Chile investigating the effect of telemedicine on efficiency and wait times found that 70% of orthopedic consultations were resolved after 2 telemedicine evaluations, and wait times for orthopedic referrals were decreased on average from 201 days to 40 days [36].…”
Section: Benefits and Challenges Of Telehealth Servicesmentioning
confidence: 99%
“…Additionally, the majority of both groups preferred telemedicine over in-clinic visits (58.8% of telemedicine group and 63.6% of standard group) [42]. A study carried out in the United Kingdom that investigated the effectiveness of a virtual joint replacement clinic found that 89% of patients were either satisfied or very satisfied with their virtual follow-up [16]. Buvik et al [9] conducted a randomized controlled trial (RCT) in Norway comparing real-time orthopedic video consultations to standard in-person visits and reported that 99% of the telemedicine group rated the encounter as very satisfactory or satisfactory.…”
Section: Benefits and Challenges Of Telehealth Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue, El Ashmawy et al. [ 1 ] report on their experience with 1749 patients who were invited to undergo a virtual follow up visit once they were more than six weeks after their hip or knee arthroplasty. The authors found that over 90% of patients utilized the virtual service at the 1 year follow up visit and only 7% of patients required an in-person visit in place of the virtual meeting.…”
mentioning
confidence: 99%